Clinical picture and long-term symptoms of SARS-CoV-2 infection in an Italian pediatric population - Silvia Bloise; Sara Isoldi; Alessia Marcellino; Enrica De Luca; Anna Dilillo; Saverio Mallardo; Vanessa Martucci; Mariateresa Sanseviero; Emanuela Del Giudice; Donatella Iorfida; Rita Leone; Alessia Testa; et al. (BMC, 2022)
Abstract Background SARS-CoV-2 infection in the pediatric age group has a milder course than in adults, but in some cases even children may present with severe forms or develop long-term consequences. The aim of this study was to analyze the clinical features, long-term effects, lifestyle changes and psychological effects of SARS-CoV-2 infection in a pediatric sample of the Italian population. Methods We conducted a telephone survey among 3075 children infected with SARS-CoV-2 in the Latina Local Health Authority. Outcomes included: clinical features of infection, long-term symptoms, lifestyle changes and emotional symptoms during the illness. The information obtained was automatically linked to a spreadsheet and analyzed. Results One thousand four hundred thirteen children agreed to participate in the study; the mean age was 112.8 ± 21.9 months. Children were infected mainly inside familial clusters (59.6%; n = 842); 99% (n = 1399) of children were asymptomatic or exhibited mild symptoms. 20% (n = 259) of children experienced long-term symptoms; risk factors were: older age, higher body mass index and longer duration of infection. Throughout the period of infection, children spent most of the time on devices like tv-video, social media and mobile phone for non-educational activities. 58.8% (n = 620) of parents expressed a negative opinion about distance learning. Finally, we observed that 49,6% (n = 532) of children experienced psychological symptoms during quarantine period. Conclusion Despite a lower susceptibility to COVID-19 in children, it is important to keep the focus high in children, both because of the possible long symptoms after infection and the impact on a children's mental and physical health due to pandemic. We believe that the return to school or other extracurricular activities are important to correct some of the risk factors for the long COVID syndrome, as obesity, and to limit the cultural damage generated by distance learning and psychological effects related to restrictive measures.